Marketing Planning in the Theory of Life Cycle - Solomyanyuk, Natalia (My University, 2013)
The origin of theory of life cycle is considered, the basic models life cycle of enterprise, stage and descriptions that determine the evolution his development are investigational. Planning features are certain in marketing depending on the stages of development enterprise.
Keywords: marketing plan; маркетинговий план; маркетинговый план; marketing planning; маркетингове планування; маркетинговое планирование; theory of life cycle; теорія життєвого циклу; теория жизненного цикла; кафедра маркетингу